(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Facial nerve palsy is the common problem of facial muscles weakness and facial appearance, mainly resulting of temporary or permanent damage of any structures innervated by the facial nerve. It can be congenital or acquired. About 45 to 75 % of unilateral facial nerve palsy cases are still idiopathic. Facial palsy impairment significantly affects swallowing, articulation, and lip sufficiency. Diminished facial expression can pose challenges in face-to-face communications that affects their psychological consequences which lead to negative impact on the quality of life. This article reviews on the assessment and management for the communication and quality of life. Speech-language therapy in facial paralysis aims in the rehabilitation of oral functions such as verbal and non-verbal communication, swallowing and vegetative skills.